Rates and sources of phosphorus and mycorrhizal fungi on the nutrition ai the 'Rangpur' lime until transplanting - Camargo, Ivo Pereira de; Souza, Maurício de; Carvalho, Janice Guedes de; Oliveira, Elizabeth de (Pesquisa Agropecuaria Brasileira, 2014)
This research was carried out at the Escola Superior de Agricultura de Lavras (ESAL), in Lavras, MG, Brazil. The objective was to study the effect of diferente rates and sources of phosphorus and inoculation with vesicular-arbuscular mycorrhizae (VAM) on the nutrition of 'Rangpur' lime, growing in seedlings until transplanting. The experimental design used was randomized blocks in split- splot scheme. The plots were composed by the inoculation treatments with the mycorrhizal fungi Acaulospora morrowae, Glomus clarum and a noninoculated control. The sub-plots were composed by the rates and sources of P 205 in a factorial scheme with the rates of 0; 320; 640 and 1280 g of P205 by m3 of substrate and two sources of phosphorus fertilizers, the single superphosphate and the apatite of Araxá. Increasing the rates of single superphosphate, made higher concentration of P and Ca in the dry matter four months after sowing, in relation to use of apatite of Araxá. The fungus Acaulospora norrowae made higher rates of root colonization and higher absorption of P, K and Zn by the plants